KLASIFIKASI SUARA JANTUNG MENGGUNAKAN DEEP LEARNING INTEGRASI AI DALAM APLIKASI WEB UNTUK DETEKSI DINI GANGGUAN KARDIOVASKULAR - nengsih, warnia; Elviyenti, Mona; Fadhli, Mardhiah; Aleanda, Galih; Utama, Nuradila (Jurnal Komputer Terapan, 2025)
Heart disease is one of the leading causes of death worldwide, making early detection crucial to prevent more serious complications. One of the methods that can be used is heart sound analysis, which contains important information related to the physiological and pathological conditions of the heart. However, the manual analysis process by healthcare professionals requires specialized skills and may result in interpretation errors. Therefore, this research aims to develop an artificial intelligence-based system using Convolutional Neural Networks (CNN) to automate heart sound classification. This system allows users to upload heart sound recordings, which will then be processed and classified as Normal or Abnormal. The research process consists of several main stages, including data collection and preprocessing of heart sounds, development and training of the CNN model, implementation of the model into a web application, and testing and evaluation of the system using metrics such as accuracy, precision, and recall. The outcome of this research includes a deep learning model for heart sound classification. The developed system is expected to enhance the accuracy and efficiency of heart disease detection, reduce reliance on manual analysis, and serve as an artificial intelligence-based solution that can be integrated into healthcare services.